Analysis of Constraints in Utilizing Classroom Reading Corners to Foster Reading Interest - Ainun Tinguli; Maryam H. Dumako (Universitas Islam Darul Ulum Lamongan, 2026)
This study investigates and analyzes the primary obstacles hindering the utilization of reading corners at SDN 02 Dengilo. Although reading corners serve as essential literacy facilities designed to cultivate a reading culture and elevate students' interest, their practical implementation has not been entirely successful. Employing a qualitative descriptive approach, data was gathered through direct observations, structured interviews with fifth-grade homeroom teachers and students, and documentation. The data was subsequently analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The findings reveal four main constraints inhibiting the effectiveness of these facilities: (1) limited and monotonous book collections, (2) intrinsically low student interest in reading, (3) the overwhelming influence of gadgets and digital media, and (4) inadequate management coupled with a lack of book updates. Collectively, these constraints result in the suboptimal utilization of reading corners in fostering student literacy.